Digital Transformation in West African SMEs: The Role of Cloud Computing and Artificial Intelligence in Enhancing Operational Efficiency - Lawal, Abdullahi; Abdulyekeen, Rilwan (Darul Yasin Al Sys, 2025)
Small and Medium-sized Enterprises (SMEs) are the backbone of West Africa’s economy, contributing substantially to employment and GDP, yet they face persistent constraints such as limited access to finance, inadequate infrastructure, and intensifying global competition. This paper examines how SMEs in West Africa are adopting digital technologies, specifically cloud computing and artificial intelligence (AI), the impact of these technologies on their operations, and the barriers that hinder wider uptake. Using a mixed-method approach that combines literature review, surveys, and interviews with SMEs in Nigeria, Ghana, and Senegal, the study analyzes patterns of technology adoption and associated operational changes. The findings indicate that the adoption of cloud computing and AI enhances scalability, supports process automation, and improves decision-making; however, overall adoption remains limited due to digital literacy gaps, unreliable internet connectivity, and the perceived high cost of digital solutions. The study concludes that digital transformation offers a critical pathway for strengthening the competitiveness and operational efficiency of West African SMEs but that structural and capability-related barriers must be addressed for its potential to be fully realized. The paper contributes to the digital transformation and SME literature by providing empirical insights from a regional context that is underrepresented in existing research and by informing strategies for SMEs, policymakers, and technology providers to promote more sustainable and inclusive adoption of cloud and AI solutions.